2018
DOI: 10.1093/ageing/afy021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Instrumental Activities of Daily Living for dementia in community-dwelling older adults

Abstract: our findings support using IADL scale to screen older community-dwelling residents for dementia: it has discriminant power comparable to that of the AD8 and MMSE. Combining the IADL and the AD8 improves specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Our findings are comparable to other recent research on the original Lawton's IADL Scale, which reported that the scale discriminated extremely well between dementia and non‐dementia groups . However, our research identified a stronger correlation between the MMSE and the Modified Lawton's Scale at 0.73 compared to 0.37 in the previous research . Similar to other research, no significant differences were found between men and women, suggesting that the Modified Lawton's Scale can be used for both sexes.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our findings are comparable to other recent research on the original Lawton's IADL Scale, which reported that the scale discriminated extremely well between dementia and non‐dementia groups . However, our research identified a stronger correlation between the MMSE and the Modified Lawton's Scale at 0.73 compared to 0.37 in the previous research . Similar to other research, no significant differences were found between men and women, suggesting that the Modified Lawton's Scale can be used for both sexes.…”
Section: Discussionsupporting
confidence: 87%
“…However, our research identified a stronger correlation between the MMSE and the Modified Lawton's Scale at 0.73 compared to 0.37 in the previous research . Similar to other research, no significant differences were found between men and women, suggesting that the Modified Lawton's Scale can be used for both sexes.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations